Innovation of Online English Learning Based on Comprehension-Centered: Transforming Learning Strategies for Junior High School Students (Universitas Terbuka, 2025)
This study explores the challenges of online English learning, where students often rely on rote memorization of vocabulary and grammar while struggling with comprehension and confidence. The purpose of this research was to design and implement a comprehension-centered approach to improve students’ understanding of meaning in digital learning contexts. Using a qualitative case study design, the research involved five seventh-grade students who participated in a three-month online private course. Data were collected through participatory observation, in-depth interviews, documentation of student work, and open and closed questionnaires. The analysis followed the Miles and Huberman model, which included data reduction, data display, and conclusion drawing, with triangulation and member checks to ensure validity. The findings indicate that students demonstrated stronger comprehension skills, such as identifying main ideas, making inferences, and reflecting on texts more meaningfully. They also showed improved confidence and active engagement through contextual discussions, project-based tasks, and reflective practices. This study contributes original insights by integrating a comprehension-centered approach with digital tools, emphasizing its adaptability and potential to transform online learning across disciplines beyond English language education. The research highlights the importance of aligning comprehension-focused strategies with educational technology to create inclusive and meaningful learning experiences in the digital era.